PENGARUH PENDAPATAN ASLI DAERAH, PENDAPATAN TRANSFER, DAN LAIN-LAIN PENDAPATAN DAERAH YANG SAH TERHADAP BELANJA MODAL (Studi Pada Pemerintah se-Kabupaten/Kota Provinsi Jawa Tengah Tahun 2017-2020) - Lula Salwa Dinah; Darsono Darsono (Diponegoro Journal of Accounting, 2023)
The results of this research showed that Local Tax and General Allocation Funds had a significant positive effect of Capital Expenditures, while Regional Retribution, Special Allocation Funds, and Other Lawful Local Revenue had a significant effect on Capital Expenditures. The purpose of this research was to examine the effect of Original Local Government Revenue consisting of Local Tax, Regional Retribution, then Transfer Revenue consisting of General Allocation Funds, Special Allocation Funds, and Other Lawful Local Revenue on Capital Expenditures. This research was conducted of capital expenditure which is important because the allocation is used to support daily activities and encourage the regional economy to progress and develop. Authors used data population is from Budget Realization Report (LRA APBD) of the regional government of the regency/city of Central Java Province in 2017-2020 which has been audited by the BPK of Central Java Province.The population and sample in this research are 35 districts/cities of Central Java Province. This research uses multiple liniear regression analysis with the number of data observations is 140 data.The results of this research showed that Local Tax and General Allocation Funds had a significant positive effect of Capital Expenditures, while Regional Retribution, Special Allocation Funds, and Other Lawful Local Revenue had a significant effect on Capital Expenditures.